Italy : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2016)
This report provides a summary of the anti-money laundering and combating the financing of terrorism (AML/CFT) measures in place in Italy as at the date of the onsite visit. It analyzes the level of compliance with the Financial Action Task Force recommendations and the level of effectiveness of Italy's AML/CFT system, and provides recommendations on how the system could be strengthened. Italy has a mature and sophisticated AML/CFT regime, with a correspondingly well-developed legal and institutional framework. Law enforcement agencies access, use, and develop good quality financial intelligence. Financial sector supervisors have been using a risk-based approach to varying degrees, but their supervisory tools could be improved.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet